Complete mitochondrial genome of leaf coral Pavona decussata (Scleractinia, Agariciidae). (2nd September 2016) - Shi, Xiaofeng; Lin, Rongcheng; Zheng, Xinqing; Liu, Xinming; Niu, Wentao
Abstract: The leaf coral Pavona decussate is a wide-spread shallow-water species of genus Pavona within Agariciidae. In our study, the entire mitochondrial nucleotide sequence of P. decussate was determined. The sequence was 18, 378 bp in length and contained 13 protein-coding genes, 2 ribosomal RNA genes (small and large mitochondrial ribosomal RNA) and 2 transfer RNA genes ( tRNA Met and tRNA Trp ). The overall base composition of the mitogenome was 23.8% A, 35.4% T, 25.4% G, and 15.4% C, with a high AT content of 59.3%, which is typical for invertebrate mtDNA. It shared 97.9%, 96.2% and 89.3% mitogenome sequence with P. clavus, Agaricia humilis and Astreopora myriophthalma, respectively.